2021
DOI: 10.3389/fphys.2021.696261
|View full text |Cite
|
Sign up to set email alerts
|

Peak Fat Oxidation Rate Is Closely Associated With Plasma Free Fatty Acid Concentrations in Women; Similar to Men

Abstract: Introduction: In men, whole body peak fat oxidation (PFO) determined by a graded exercise test is closely tied to plasma free fatty acid (FFA) availability. Men and women exhibit divergent metabolic responses to fasting and exercise, and it remains unknown how the combined fasting and exercise affect substrate utilization in women. We aimed to investigate this, hypothesizing that increased plasma FFA concentrations in women caused by fasting and repeated exercise will increase PFO during exercise. Then, that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…(f) Previous exercise increases MFO Consistent with the abovementioned observation that CHO oxidation blunts fat oxidation during exercise and that this effect is reversed when the CHO supply to muscles is decreased, previous exercise of 1 h has been shown to result in an increase in MFO [119]. Interestingly, this effect is no longer found after 2 days of fasting [150].…”
Section: Effects Of Exercise and Training On Lipid Oxidationsupporting
confidence: 77%
See 3 more Smart Citations
“…(f) Previous exercise increases MFO Consistent with the abovementioned observation that CHO oxidation blunts fat oxidation during exercise and that this effect is reversed when the CHO supply to muscles is decreased, previous exercise of 1 h has been shown to result in an increase in MFO [119]. Interestingly, this effect is no longer found after 2 days of fasting [150].…”
Section: Effects Of Exercise and Training On Lipid Oxidationsupporting
confidence: 77%
“…In a study on 304 subjects [128], we compared exercise calorimetry results among athletes, sedentary, and type 2 diabetics, in whom men and women were matched for age, BMI, and physical activity, and we found that the LIPOXmax occurs at a higher percentage of VO 2max in female athletes and sedentary women compared to men. However, MFO expressed for fat-free mass or muscle mass did not differ between men and women, as recently confirmed by Frandsen and coworkers [150]. In the review by Maunder and coworkers [14], gender, but not age, is considered a major determinant of the LIPOXmax, while Amaro-Gahete and coworkers [181] clearly confirm the influence of gender but indicate that participants' age should be considered when providing normative values.…”
Section: Age and Gendermentioning
confidence: 64%
See 2 more Smart Citations
“…Indeed, a rapid metabolite turnover can be detected in seconds after an acute bout of endurance exercise, whereas it takes minutes to hours for transcriptomic and proteomic responses accounting for training adaptation [ 21 ]. An increase of about 75% of the maximum rate of fat oxidation (whole body measure), which is already high in elite endurance athletes, is observed after a 2 h recovery in a fasting condition from an endurance exercise session [ 22 , 23 , 24 ]. As both exercise and GW0742 alter fatty acid availability, we considered it important to choose the most appropriate experimental conditions in mice that allowed discriminating GW0742 effects from those induced by exercise, considering that the signature of an increase in FAO in T cells would be interpreted in an individual athletes’ biological passport [ 25 ] as a doping signature.…”
Section: Discussionmentioning
confidence: 99%